Sodium Channel Myotonia Due to Novel Mutations in Domain I of Nav1.4 - Pagliarani, Serena; Lucchiari, Sabrina; Scarlato, Marina; Redaelli, Elisa; Modoni, Anna; Magri, Francesca; Fossati, Barbara; Previtali, Stefano C.; Sansone, Valeria A.; Lecchi, Marzia; Lo Monaco, Mauro; Meola, Giovanni; et al. (Frontiers in Neurology, 2020)
Sodium channel myotonia is a form of muscle channelopathy due to mutations that affect Nav1.4 channel. We describe seven families with a series of symptoms ranging from asymptomatic to clearly myotonic signs that have in common two novel mutations, p.Ile215Thr and p.Gly241Val, in the first domain of Nav1.4 channel. The families described have been clinically and genetically evaluated. p.Ile215Thr and p.Gly241Val lie respectively on extracellular and intracellular loops of the first domain of the Nav1.4 channel. We assessed that the p.Ile215Thr mutation can be related to a founder effect in people from Southern Italy. Electrophysiological evaluation of the channel function showed that the voltage-dependence of the activation for both the mutant channels was significantly shifted toward hyperpolarized potentials (Ile215Thr:-28.6 ± 1.5 mV and Gly241Val: -30.2 ± 1.3 mV versus WT:-18.5 ± 1.3 mV). The slow inactivation was also significantly affected, whereas fast inactivation showed different behavior in the two mutants. We characterized two novel mutations of SCN4A gene expanding the knowledge about genetics of mild forms of myotonia and we present, to our knowledge, the first homozygous patient with sodium channel myotonia.